Cytotoxic secondary metabolites isolated from Penicillium sp. YT2019-3321, an endophytic fungus derived from Lonicera Japonica - Weng, Wenya; Jiang, Shicui; Sun, Chuchu; Pan, Xiaofu; Xian, Li; Lu, Xuemian; Zhang, Chi (Frontiers in Microbiology, 2022)
Introduction Endophytic fungi associated with medicinal plants have proven to possess a high potential to produce structurally diverse metabolites, some of which are valuable for medicinal applications. In this study, Penicillium sp. YT2019-3321, an endophytic fungus derived from traditional Chinese medicine Lonicera japonica, was chemically studied. Methods The chemical structures of the isolated compounds were established by a correlative interpretation of HRESIMS and NMR spectroscopic data. The optical resolution of (±)-1 by chiral HPLC yielded individual enantiomers (+)-1 and (–)-1, and their stereochemistry were solved by X-ray diffraction crystallography, respectively. Results and discussion Eight structurally diversified secondary metabolites, including two previously unreported polyketides, named (±)-chrysoalide B (1) and penicidone E (2), were isolated and identified from Penicillium sp. YT2019-3321. Compound 2 possessed the γ-pyridone nucleus, which is rarely found in natural products. Cytotoxic assay revealed that the new compound 2 demonstrated a dose-dependent cytotoxicity against the human pancreatic tumor cells PATU8988T with the IC50 value of 11.4 μM. Further studies indicated that 2 significantly induced apoptosis of PATU8988T cell lines, characterized by the morphologies abnormity, the reduction of cell number, the upregulation of proportion of apoptotic cells, and the ratio of Bcl-2 to Bax. Our study demonstrates that fungal secondary metabolites may have important significance in the discovery of drug leads.